DEVELOPMENT OF SMART WELL UNITS FOR MULTILAYER RESERVOIRS OPERATED WITH THE SYSTEM OF SIMULTANEOUS-SEPARATE EXPLOITATION - Lushpeev, Vladimir Aleksandrovich; Khmelenko, Polina Pavlovna; Tsiku, Iurii Kimovich; Tananykhin, Dmitrii Sergeevich (Journal of Applied Engineering Science, 2018)
The paper shows a new approach to oilfields development. The advantages of multilayer reservoir facilities equipped with the system of simultaneous-separate exploitation are presented. New units are suggested to be applied in order to correspond the whole range of possibilities in the sphere of «smart wells». The devised fluid choking device allows changing flow characteristics without interfering in a borehole while the usage of simultaneous-separate exploitation facility allows monitoring the development of each individual layer witihin a multilayer object.